Research results proving the dependence of the copper concentrate amount recovered from basalt raw material on the electric separator field intensity - Naduty, Vladimir; Malanchuk, Zinovii; Malanchuk, Yevhenii; Korniyenko, Valerii (Eastern-European Journal of Enterprise Technologies, 2016)
The study proves the efficiency of using electric separation for extracting the copper concentrate from a crushed mass of basalt, lava-breccia, and tuff after their preliminary magnetic separation. We have determined the preferred particle-size classes (–1.0 +0.63 mm) in the processes of preparing the ore and classifying the components of the basaltic rock mass (from –0.25 +0.05 mm to –1.0 +0.63 mm) before electric separation; the copper concentrate outputs have been specified for basalt, tuff, and lava-breccia with regard to the electric field voltage for different particle-size fractions in the initial product. The undertaken tests have revealed a linear dependence of the native copper output on the electric field voltage of the separator, which must be taken into account while developing the technological scheme of extracting native copper from basaltic raw materials. We have proved that all the three components of the basaltic raw material (basalt, lava-breccia, and tuff) contain some percentage of copper that is of commercial interest. To extract substantial amounts of copper, it is essential to have a specific particle-size composition of the basaltic raw material before feeding it into the electric separator (basalt – 10.370 %, lava-breccia – 5.741 %, and tuff – 4.074 %; thereby, the particle size class of the feedstock is –1.0 +0.63 mm, and the electric field voltage is 30 kW). The obtained findings help develop the basic requirements for industrial tests. It is expedient to carry out more field tests and to create an industrial site for a complex processing of basalt raw materials. The completed study is a necessary element of developing a non-waste technology of processing the basalts of the Rafalovsky basalt quarry in Ukraine. In addition to native copper, these deposits contain such useful components as iron, titanium, manganese, and a silicate part. While extracting strategically valuable raw materials, the ecological situation in the region is improved due to the processing of industrial wastes such as tuff and lava-breccia.